Strategi Bimbingan dan Pengembangan Dalam Membentuk Keluarga Hita Sukhaya (Maitreyani) Bagi Pasangan Muda Perkawinan Umat Buddha Di Maha Vihara Maitreya Kota Pekanbaru - Sonika Sonika; Hosan Hosan; Rida Jelita; Irawati Irawati; Suryati Suryati (STAB Maitreyawira, 2023)
This study aims to describe the understanding of Hita Sukhaya (Maitreyani) family for young couples by guidance and development strategies using SWOT analysis. The case study qualitative research design, based on purposive sampling of 5 Buddhist couples. Data analysis with interactive model (Miles and Huberman, 1994), data validity with triangulation validation and member check. The results showed that young Buddhist couples in Pekanbaru fully understood how to implement the blessing at Maitreya Monastery to formalize the Hita Sukhaya (Maitreyani) family, so there would be spiritual bond to obtain the Buddha's blessing to build a harmonious family, realizing Universal Family. The strategic role of the Monastery in providing services to formalize the Maitreyani Family as the main goal and function which is also an opportunity from available human resources to turn potential programs into effective programs in service.